The Effectiveness of Acupressure Therapy in Lowering Blood Pressure in Patients with Hypertension - Zubaidah Zubaidah; Insana Maria; Rusdiana Rusdiana; Iis Pusparina; Raihana Norfitri (Universitas Airlangga, 2021)
Introduction: Hypertension is a non-communicable disease that affected on health in the adult age group. Acupressure therapy that can improve blood circulation for people with hypertension. Acupressure therapy can be an alternative treatment option to lower blood pressure and can meet the needs of society in reducing pharmacological therapy. The study was to determine the effect of Acupressure on changes in blood pressure of hypertension sufferers.Method: This study used pre-experimental design. The number of respondents was 15 people with consecutive sampling technique. The research variable is acupressure therapy. While the dependent variable is blood pressure. The data collected are primary data using observation sheets and blood pressure measured with a tensimeter and a stethoscope before and after the intervention. Therapy is done 3 times for 3 three days.Results: The results of the study showed that there was an effect of changes in blood pressure before and after being given acupressure therapy with p = 0.046 and p = 0.003.Conclusion: Acupressure is a simple non-invasive technique that nurses can perform independently. These findings suggest that acupressure can reduce systolic and diastolic blood pressure in patients with hypertension. The further research regarding acupressure therapy for other diseases besides hypertension.